Synthesis of Polyfunctionalized 4H-Pyrans - Manisha Bihani; Pranjal P. Bora; Ghanashyam Bez (Journal of Chemistry)
Amberlyst A21 catalyzed one-pot three-component coupling of aldehyde and malononitrile with active methylene compounds such as acetylacetone and ethyl acetoacetate for the synthesis of pharmaceutically important polyfunctionalized 4H-pyrans has been reported. Simple experimental procedure, no chromatographic purification, no hazardous organic solvents, easy recovery and reusability of the catalyst, and room temperature reaction conditions are some of the highlights of this protocol for the synthesis of pharmaceutically relevant focused libraries.